Pengaruh Self Efficacy dan Pelatihan Kerja terhadap Kinerja Karyawan pada PT Telemedia Dinamika Sarana Jakarta Barat - Syifa Ratna Dewati; Bachtiar Arifudin Husain (Universitas 45 Surabaya, 2025)
The purpose of this study was to determine the effect of self-efficacy and job training on employee performance at PT Telemedia Dinamika Sarana West Jakarta, both partially and simultaneously. The research method used is an associative quantitative method. The population in this study were all 86 employees of PT Telemedia Dinamika Sarana West Jakarta, and the sampling technique used saturated sampling, namely the entire population was sampled. Data analysis was carried out using the SPSS version 25 program, with analysis techniques in the form of simple linear regression, multiple linear regression, T test (partial), F test (simultaneous), correlation coefficient, and coefficient of determination. The results showed that there was a significant partial influence between self-efficacy on employee performance. This was evidenced by the calculated t value of 11.371> t table 1.988, and a significance level of 0.000 <0.05, so that H₀₁ was rejected and Hₐ₁ was accepted. Furthermore, there is a partial significant influence between job training on employee performance, as evidenced by the calculated t value of 20.441> t table 1.988 and a significance level of 0.000 <0.05, so that H₀₂ is rejected and Hₐ₂ is accepted. While simultaneously, self-efficacy and job training have a significant effect on employee performance. This is evidenced by the calculated F value of 208.538> F table 3.110, and a significance level of 0.000 <0.05, so that H₀₃ is rejected and Hₐ₃ is accepted. The results of the determination coefficient test (R Square) show a value of 0.834, which means that self-efficacy and job training contribute to employee performance by 83.4%, while the remaining 16.6% is influenced by other variables not examined in this study.